2019
DOI: 10.1016/j.rmcr.2019.100835
|View full text |Cite
|
Sign up to set email alerts
|

Delftia acidovorans: A rare cause of septic pulmonary embolism from catheter-related infection: Case report and literature review

Abstract: Septic pulmonary emboli is a rare condition due to the dislodgement of an infected thrombus traveling to the pulmonary vasculature via the venous system. Staphylococcus spp. and Candida spp. are the most common causative agents. The most common risk factor is intravenous drug abuse, but there has been an association with intravenous catheters. Delftia acidovorans (DA) is a rare organism causing catheter-related infection, which has a tendency to embolize and clog up major vessels. It is highly resistant to all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
10
0
4
Order By: Relevance
“…were found with an abundance of almost 6% and 2%, respectively. Delftia acidovorans is usually not pathogenic, but catheter-related bacteremia and cases of pneumonia with lung cavity formation has been observed ( 23, 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…were found with an abundance of almost 6% and 2%, respectively. Delftia acidovorans is usually not pathogenic, but catheter-related bacteremia and cases of pneumonia with lung cavity formation has been observed ( 23, 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nor is it well understood whether the presence of Delftia in water systems is problematic or potentially beneficial. Like many bacterial taxa, Delftia species are recorded as opportunistic pathogens that can infect hospitalized or immunocompromised patients (Patel et al, 2019) (Bilgin et al, 2015. However, there is no indication that human bodies are a common habitat for this genus.…”
Section: Discussionmentioning
confidence: 99%
“…This patient with symptoms of lower respiratory tract infection died despite treatment 5 . The reported cases of Delfia infection consist mostly of patients with immunodeficiency 2,16,17 However, there are also cases reported in immunocompetent patients 3,5,18 . Khan et al 3 , reported a case of Delftia acidovorans bacteremia, in a four-year-old immunocompetent patient with pulmonary abscess.…”
Section: Discussionmentioning
confidence: 99%